2022
DOI: 10.3390/nano12203564
|View full text |Cite
|
Sign up to set email alerts
|

Mg-Doped ZnO Nanoparticles with Tunable Band Gaps for Surface-Enhanced Raman Scattering (SERS)-Based Sensing

Abstract: Semiconductors have great potential as surface-enhanced Raman scattering (SERS) substrates due to their excellent physiochemical properties. However, they provide low signal enhancements relative to their plasmonic counterparts, which necessitates innovation in their synthesis and application. Substitutional atomic doping is proposed to improve SERS enhancement by controlling electronic properties, such as the band gap. In this work, zinc oxide (ZnO) nanoparticles were synthesized by co-precipitation and doped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The synthesized substrates' UV-visible absorption spectra were obtained to determine their optical properties. As shown in Figure 4, all spectra showed an absorption band at 358 nm, corresponding to ZnO [21]. For the ZnO-Au samples, a broad band was observed at 560 nm, corresponding to Au nanoparticles and thereby indicating that the ZnO-Au substrates are active in both the ultraviolet and visible light region [22].…”
Section: Synthesis and Characterization Of Au-coated Znomentioning
confidence: 90%
See 2 more Smart Citations
“…The synthesized substrates' UV-visible absorption spectra were obtained to determine their optical properties. As shown in Figure 4, all spectra showed an absorption band at 358 nm, corresponding to ZnO [21]. For the ZnO-Au samples, a broad band was observed at 560 nm, corresponding to Au nanoparticles and thereby indicating that the ZnO-Au substrates are active in both the ultraviolet and visible light region [22].…”
Section: Synthesis and Characterization Of Au-coated Znomentioning
confidence: 90%
“…[23,24,28]. The high-resolution spectrum of O can be split into two Gaussian peaks, as shown in Figure 3d; the peak centered around 530.62 eV corresponds to O −2 on the wurtzite structure of Zn 2+ , while the peak centered around 532.42 eV can be attributed to oxygen vacancies [21]. Overall, the XPS analysis indicated that Au was associated with ZnO, which could thereby provide the electromagnetic contribution towards the enhancement of Raman signal in subsequent applications.…”
Section: Synthesis and Characterization Of Au-coated Znomentioning
confidence: 99%
See 1 more Smart Citation
“…To confirm the chemical compositions and valence states of the synthesized ZnO-NPs, x-ray photoelectron spectroscopy (XPS) was used as displayed in figures and the 532 eV peak is related to the adsorbed oxygen (chemisorbed oxygen) at the surface [43][44][45][46][47][48][49][50]. It can be observed the initial O 1s peak has FWHM as 2.94 eV after the fit curve it decreases to 1.43 eV for each peak.…”
Section: Electrochemical Measurementsmentioning
confidence: 99%